1998
DOI: 10.1063/1.869571
|View full text |Cite
|
Sign up to set email alerts
|

The generation of two-dimensional vortices by transverse oscillation of a soap film

Abstract: An experimental investigation of the dynamics of horizontal soap films stretched over circular or square boundaries undergoing periodic transverse oscillations at frequencies in the range 20–200 Hz is reported. Concomitant with modes of transverse flexural oscillations, it was observed that two-dimensional vortices in the plane of the film are excited. The vortices may be either (i) large, scaling with the size of the cavity or (ii) small, localized at a wavelength or half-wavelength of the membrane modes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 12 publications
5
45
0
1
Order By: Relevance
“…It is well known that the air around the soap film considerably changes its dynamics. Inspired by papers [5,6], we consider an influence of air to the motion of the thin smectic film and, particular, to the mechanism of the vorticity generation.…”
Section: Film In Vacuummentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the air around the soap film considerably changes its dynamics. Inspired by papers [5,6], we consider an influence of air to the motion of the thin smectic film and, particular, to the mechanism of the vorticity generation.…”
Section: Film In Vacuummentioning
confidence: 99%
“…Fortunately, dynamics of the smectic films is simpler than one of the soap films since there is no analog of Marangoni waves [5] in the case. It allows us to construct a quantitative theory of the phenomenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several authors have shown that air inertia plays a major role on soap film vibrations (Couder, Chomaz & Rabaud, 1989, Rutgers et al, 1996, Afenchenko et al, 1998, Kosgodagan Acharige, Elias & Derec, 2014. Indeed, the film displaces a mass of air that scales like ρ a a 3 (the radius of the film a being the only relevant length scale, and ρ a being the density of air), whereas the mass of the film itself scales like ρea 2 .…”
Section: Dynamics Of the Horizontal Filmmentioning
confidence: 99%
“…In practice, in our experiments the latter is always dominant (the first two effects are approximately ten times weaker than the third one), and simple geometry allows us to correlate the position of the laser spot on the sensor to the local slope of the film in L. Given the range of excitation forcing frequencies tested in this work, the film features an axisymmetric deformation. We have checked that more complex, non-axisymmetric patterns, such as the ones shown in Couder, Chomaz & Rabaud, 1989, Afenchenko et al, 1998, Vega, Higuera & Weidman, 1998, Elias, Hutzler & Ferreira, 2007, appear on the film only above 200 Hz. This allows us to deduce, from this measure of a local slope, its entire profile, see equation (3.13) for the predicted axisymmetric profile.…”
Section: Setupmentioning
confidence: 99%